The Learning Model of Islamic Educational Management at STIT Mambaul Ulum Jambi - M. Shoffa Saifillah Al Faruq; Ahmad Sunoko (Didaktika Religia, 2021)
This article aims to describe the reasons for Sekolah Tinggi Ilmu Tarbiyah (STIT) Mambaul Ulum Jambi in implementing the learning model of Islamic educational management. A qualitative approach in the form of a case study is used in this research. Techniques in collecting data are observation, interview, and documentation. The data is analyzed using the interactive analysis technique of Miles and Huberman. The triangulations of source and method are used to test the validity of data. The results show that the learning model of Islamic educational management at STIT Mambaul Ulum Jambi is based on the desire to change the students' character to be independent, have high selfconfidence in facing problems, and foster students' hope is more optimistic about the future. The results also show that in implementing the learning model of Islamic educational management, STIT Mambaul Ulum uses teacher-centered learning combined with student-centered learning. It implements a conventional method with various techniques adapted to the learning situation and condition.